Twenty-four-hour efficacy of preservative-free tafluprost for open-angle glaucoma patients, assessed by home intraocular pressure (Icare-ONE) and blood-pressure monitoring - Cho, Soon Young; Kim, Yong Yeon; Yoo, Chungkwon; Lee, Tae-Eun (Japanese journal of ophthalmology, 2016)
Purpose To evaluate the effect of preservative-free (PF) tafluprost on diurnal variation of intraocular pressure (IOP) and ocular perfusion pressure (OPP), measured by use of home IOP and blood-pressure (BP) monitoring devices, for primary open angle glaucoma (POAG) patients. Methods Twenty-two eyes from 22 patients with POAG were studied. Initially, IOP was measured at the hospital by Goldmann applanation tonometry (GAT) and Icare-ONE rebound tonometry. Each patient was then instructed how to use the Icare-ONE and BP home monitoring devices. IOP and BP were measured at home by the patients, every 4 h, before and 2 weeks after once daily treatment with PF tafluprost (0.0015 %) ophthalmic solution. Results Intraclass correlations between different IOP measurements were greater than 0.8. PF tafluprost reduced mean diurnal IOP significantly for patients with POAG, from 15.7 ± 1.2 mmHg at baseline to 12.5 ± 0.6 mmHg 2 weeks after treatment ( p < 0.001). It increased mean diurnal OPP from 48.5 ± 7.3 mmHg at baseline to 51.3 ± 7.0 mmHg post-treatment ( p < 0.017). Conclusions Icare-ONE enables glaucoma patients to measure their own diurnal IOP fluctuations. Patient-measured Icare-ONE IOP readings showed that PF tafluprost effectively reduced diurnal IOP in eyes with POAG.